Visualizing relative position of two straight lines in space: An exploratory study of the anaglyph in GeoGebra - Tang Minh Dung; Le Thai Bao Thien Trung; Nguyen Thi Nga (Journal of Pedagogical Research)
This study investigates whether Vietnamese students face specific challenges when visualizing skew versus intersecting lines and whether using the anaglyph feature of GeoGebra can help overcome these difficulties. Employing a design-based research approach over four phases with 12th-grade students, the study involved tasks in traditional paper-pencil and GeoGebra’s anaglyph environment, which offers 3D depth perception through color separation. The findings showed an improvement in students’ accuracy in spatial visualization on 2D surfaces after using anaglyphs, as they were better able to interpret the relative positions of lines in space. This research highlights the potential of low-cost, accessible digital tools like the anaglyph feature of GeoGebra in enhancing spatial understanding in educational systems with limited resources. The insights gained from this study contribute to geometry education by demonstrating how anaglyph representations can aid in 3D visualization.